ANALISIS KRITIK SOSIAL TERHADAP PERAN PEREMPUAN DALAM NOVEL ‘BUMI MANUSIA’ KARYA PRAMOEDYA ANANTA TOE (1890-1910) - Winda Adelia Putri; Aulia Fitriany; M. Khusni Mubarak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the social critique of the role of indigenous women in Pramoedya Ananta Toer’s novel Bumi Manusia during the colonial period of 1890–1910, to identify forms of social critique directed at colonialism and patriarchy through the character of Nyai Ontosoroh, and to analyze the positive and negative impacts of her resistance. This study employs a descriptive-analytical qualitative method using a library research approach. Primary data consists of dialogue excerpts and narrative passages from the novel, supplemented by secondary sources from academic journals and history books. The analysis was conducted in three stages: data reduction, data presentation, and drawing conclusions, with validation through triangulation of sources and theory. The results of the study show that the novel Bumi Manusia serves as a powerful medium for social criticism of structural injustices during the colonial era. The character Nyai Ontosoroh represents an indigenous woman who possesses critical awareness and the capacity for resistance amid layered oppression resulting from the interplay of Javanese patriarchy and Dutch colonialism. Her resistance had a positive impact in the form of a shift in the perspectives of those around her, but it also had negative consequences, including an identity crisis and systemic failures that revealed the limits of individual resistance against totalitarian colonial power.